The Krushinsky – Molodkina genetic rat strain as a unique experimental model of seizure states - I. I. Poletaeva; Z. A. Kostyna; N. M. Surina; I. B. Fedotova; Z. A. Zorina (Вавиловский журнал генетики и селекции)
The study of genetic mechanisms, which underlie normal and abnormal behavioral traits, are important not only for fundamental knowledge of CNS function, but also for human well-being, as well as in the aspect of treatment of brain diseases. Accumulation of knowledge concerning the functions of genes, which are expressed in the CNS and are involved in the specific brain functions determined now by the success of molecular genetics, but it could not overshadow the importance of phenotype expression investigation of genetically determined traits, especially pathological ones. Epilepsy, as one of CNS diseases, occupies an important place in the row of these studies. In spite of numerous anticonvulsant drugs a significant proportion of epilepsy cases are still resistant to drug treatments. It means that the study of various aspects of epileptogenesis using animal models should be welcomed as it will help to elucidate those aspects of increased seizure proneness that are now out of scope of research attention. The distinct trait of this domain, which is not easy to analyze genetically, is audiogenic epilepsy (the seizure attack in response to loud sound). The important feature of audiogenic epilepsy is that the intense tonic seizures could be induced and analyzed repeatedly which makes it possible to induce the seizures repeatedly in the course of chronical experiments with the same animal, which is not possible in the cases of pharmacologically or electrically induced seizures. The Krushinsky – Molodkina (KM) inbred rat strain, which was the first among strains selected for audiogenic epilepsy, is briefly characterized. The specific seizure pattern, the rodent proneness for audiogenic epilepsy, as well as abnormal postictal states (catalepsy, in particular) illustrate the importance of this phenomenon not only as a model of certain brain pathology, but also as a matter of general biological importance. The importance of genetic background factor (demonstrated in the case of study of comorbidity (audiogenic epilepsy, anxiety and depression)) could be crucial in the studies of other CNS anomalies. The audiogenic seizures as a physiological phenomenon which often accompanies several brain pathologies had been in the scope of research interests for D.K. Belyaev and his colleagues in his Institute.